ANALISIS DEL LAS FUNCIONES DEL PERSONAL DE ENFERMERIA EN EL MONITOREO HEMIDINAMICO EN PACIENTES CRITICOS POST QUIRURGICOS - PERALTA DAVILA, KARLA MONICA (2021)
This thesis analyzes the importance of hemodynamic monitoring allows us to obtain information on the cardiovascular functioning of the critical patient, which is why it constitutes a fundamental piece in the diagnostic approach and in the therapeutic guide of the patient with tissue hypoperfusion. Furthermore, that is why hemodynamic monitoring provides data that will help nurses in the assessment, planning and implementation of nursing care. This work is based on describing the role of Nursing in the hemodynamic monitoring of the pediatric cardiac post-surgical patient of the Regional Hospital of Ica 2021. The present investigation is of a non-experimental type, since the independent variable is not modifiable or manipulable. Within the methodological framework, a quantitative, descriptive and cross-sectional approach, applied to the deductive-inductive method, is applied to 21 people from the cardiology department, to whom the questions were formulated in order to know the care they apply with the patients they serve. Statistical data were acquired as a percentage, represented in bars and tables. The information obtained regarding nursing care in hemodynamic monitoring provides guidelines on how to improve or strengthen skills in the healthcare field, scientific knowledge and simultaneously contribute to the research area of the health sector. KEY WORDS: Hemodynamic monitoring, critical patient, cardiovascular.